The Influence of Digital Short Story Videos on English Learning Interests of Grade 10 Students at SMAN 4 Blitar - Widya Puji Handini; Yusniarsi Primasari; Miza Rahmatika Aini (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
This study aims to explore the effect of digital short story videos on the interest in learning English of 10th grade students at SMAN 4 Blitar. Using a descriptive qualitative approach, data were collected through observation, questionnaires, and interviews with students and teachers. The results showed that internal factors such as health, motivation, and intelligence, as well as external factors such as family support and teaching quality, play an important role in increasing students' interest in learning. The use of digital short story videos was proven to be significant in increasing students' interest, with 91% of students stating that the videos were interesting. These findings suggest that digital media can be an effective tool in increasing engagement and learning outcomes.